Myeloperoxidase and Eosinophil Peroxidase Inhibit Endotoxin Activity and Increase Mouse Survival in a Lipopolysaccharide Lethal Dose 90% Model - Robert C. Allen; Mary L. Henery; John C. Allen; Roger J. Hawks; Jackson T. Stephens (Journal of Immunology Research)
Myeloperoxidase (MPO) and eosinophil peroxidase (EPO) are cationic haloperoxidases with potent microbicidal and detoxifying activities. MPO selectively binds to and kills some Gram-positive bacteria (GPB) and all Gram-negative bacteria (GNB) tested. GNB contain endotoxin, i.e., lipopolysaccharide (LPS) comprising a toxic lipid A component. The possibility that MPO and EPO bind and inhibit the endotoxin of GNB was tested by mixing MPO or EPO with LPS or lipid A and measuring for inhibition of endotoxin activity using the chromogenic Limulus amebocyte lysate (LAL) assay. The endotoxin-inhibiting activities of MPO and EPO were also tested in vivo using an LPS 90% lethal dose (LD90) mouse model studied over a five-day period. Mixing MPO or EPO with a fixed quantity of LPS from Escherichia coli O55:B5 or with diphosphoryl lipid A from E. coli F583 inhibited LAL endotoxin activity in proportion to the natural log of the MPO or EPO concentration. MPO and EPO enzymatic activities were not required for inhibition, and MPO haloperoxidase action did not increase endotoxin inhibition. Both MPO and EPO increased mouse survival in the LPS LD90 model. In conclusion, MPO and EPO nonenzymatically inhibited in vitro endotoxin activity using the LAL assay, and MPO and high-dose EPO significantly increased mouse survival in a LPS LD90 model, and such survival was increased in a dose-dependent manner.